Różnice w czeskich i polskich przekładach na przykładzie biblijnego reprezentanta awifauny – żurawia - Hampl, Lubomír (Bohemistyka, 2020)
In this article, based on sixteen various biblical trans la tions (eight Czech and eight Polish) ex clu si ve ly referring to two Old Testament verses, the author tries to present the trans la tio nal dif feren ces in avifauna paying special attention to its re pre sen ta tive – a crane. The author focuses on various aspects of trans la tio nal dif feren ces both in ter a lin guis tic and in ter lin guis tic as well as on the es ta blished image and the deep- roo ted symbolism of the described re - pre sen ta tive of the semantic category of fowl, which is the lexically basic crane.